Axis, a Flemish project on contemporary art in Indonesia and Singapore. - Gravensteen, Gent; Cemeti Gallery, Yogyakarta; National Gallery, Jakarta; Exhibition. Axis, a Flemish project on contemporary art in Indonesia and Singapore (1). Exhibition. Axis, a Flemish project on contemporary art in Indonesia and Singapore (2). Exhibition. Axis, a Flemish project on contemporary art in Indonesia and Singapore (3). Exhibition. Axis, a Flemish project on contemporary art in Indonesia and Singapore (4). Cemeti Gallery. Gravensteen Gent. Lassale SIA College of the Arts Singapura. National Gallery Jakarta. Tra-Mundi non-profit organisation Gent. 1997-06-06. 1997-08-01. 1997-09-10. 1997-11-28. 1997-06-08. 1997-08-23. 1997-09-24. 1997-12-14. + Bentara Budaya, Musium Affandi, Ardiyanto Gallery 1997-08-01 t/m 1997-08-08, 1997-08-01 t/m 1997-08-23; Cortàzar, Julio; De Baere, Bart; Huangfu, Binghui; Jaarsma, Mella; Martens, Luc; Oeghoede, Dirk; Pirotte, Philippe; Rubenstein, Alan; et al. (Gent : Tra Mundi 1997., 1997)
Het Project : Ontstaan, De Gentse tentoonstelling, Indonesië Yogyakarta, Jakarta, Singapore, Het belang van het project Axis, De toekomst, De samenwerking, Financieel, Besluit en suggesties, B. persartikels
Bijtebier, Jean-Marie ; Blondeel, Maria ; Braeckman, Dirk ; De Boe, Rik ; de Meester, Karel ; De Wit, Johan ; D'Hondt, Lieve ; Meyers, Koen ; Boelens, Peter ; Oeghoede, Dirk ; De Kerkhove, Karien Van ; Van Roy, Johan ; Vercaemer, Koen
biog. [1 p.] per kunstenaar
Axis, Gravensteen, Gent, 6-8 juni 1997 / Cemeti Gallery, Yogyakarta, 1-8 & 1-23 August 1997 / National Gallery, Jakarta, 10-24 September 1997 / Lassale SIA College of The Arts, Singapura, 28 November & 14 December 1997
Engels
Nederlands
boek
Keywords: België; Indonesië; Singapore; Vlaanderen